Sex-related differences in ventricular remodeling after myocardial infarction. (15th September 2021) - Aimo, Alberto; Panichella, Giorgia; Barison, Andrea; Maffei, Silvia; Cameli, Matteo; Coiro, Stefano; D'Ascenzi, Flavio; Di Mario, Carlo; Liga, Riccardo; Marcucci, Rossella; Morrone, Doralisa; Olivotto, Iacopo; et al.
Abstract: The epidemiology, clinical features and outcome of myocardial infarction (MI) display significant differences between men and women. Prominent sex differences have also been suggested in left ventricular (LV) remodeling after MI. Ventricular remodeling refers to a deterioration of LV geometry and function often leading to heart failure (HF) development and an increased risk of adverse cardiovascular events. Women have a lower propensity to the acquisition of a spherical geometry and LV dysfunction. These differences can be attributed at least partially to a lower frequency of transmural infarction and smaller areas of microvascular obstruction in women, as well as to a less prominent activation of neuroendocrine systems and apoptotic, inflammatory and profibrotic pathways in women. Estrogens might play a role in this difference, which could partially persist even after the menopause because of a persisting intramyocardial synthesis of estrogens in women. Conversely, androgens may exert a detrimental influence. Future studies should better clarify sex differences in the predictors, clinical correlates, prognostic impact and disease mechanisms of remodeling, as well as the existence of sex-specific therapeutic targets. This research effort should hopefully allow to optimize the treatment of MI during the acute and post-acute phase, possibly through different therapeutic strategies in men and women, with the goal of reducing the risk of HF development and improving patient outcome. Highlights: The ventricular remodeling after MI differs between men and women. Women have a lower propensity to remodeling. Estrogens might contribute to this gender difference. Gender-specific therapeutic targets have not emerged so far.